2015
DOI: 10.1177/0886260515596535
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluations and Victim Satisfaction With State Compensation for Violent Crime: A Prospective Study

Abstract: Satisfaction with a particular good or service represents an affective state in response to an individual's evaluation of the performance of that good or service. This evaluation involves a comparison between perceived actual performance and prior expectations. The current study used this theoretical idea to study violent crime victims' levels of satisfaction with services provided by a Dutch state compensation scheme. One hundred and seventy-seven victims of violent crime who had applied for compensation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It may also explain why only an estimated average of 16% 6 of clients applied for compensation. While seemingly low, however, this is actually higher than the estimated 5% of eligible victims thought to claim compensation in the United Kingdom (Committee of Public Accounts, 2008) and is closer to the high uptake rate of 20% in the Netherlands (Kunst, Koster, & van Heugten, 2015). It is unclear why this might be, but could relate to having ISVAs provide information and support, especially in light of clients' initially limited awareness.…”
Section: Before the Application: Decisions About Claiming Compensationmentioning
confidence: 80%
“…It may also explain why only an estimated average of 16% 6 of clients applied for compensation. While seemingly low, however, this is actually higher than the estimated 5% of eligible victims thought to claim compensation in the United Kingdom (Committee of Public Accounts, 2008) and is closer to the high uptake rate of 20% in the Netherlands (Kunst, Koster, & van Heugten, 2015). It is unclear why this might be, but could relate to having ISVAs provide information and support, especially in light of clients' initially limited awareness.…”
Section: Before the Application: Decisions About Claiming Compensationmentioning
confidence: 80%
“…She further argues that victims view compensation as a symbolic acknowledgement of their loss and suffering. A study conducted in the Netherlands supported the idea that victim satisfaction with the justice system partly depends on whether compensation was received (Kunst et al, 2017). In a study of Israeli victims, Aviv and Weisburd (2016) found that victims tend to hold more negative attitudes toward the police than the general population, but they argue that this gap can be overcome by police efforts to address the needs and rights of victims.…”
Section: Introductionmentioning
confidence: 99%
“…Victims’ satisfaction was also related to the fact that their request was approved, but it was not related to the amount they received or their evaluations of it. The authors interpret the latter finding as reinforcing Mulder (2013): it is not so much the amount of money but ‘some kind of recognition for the harm suffered’ (Kunst et al, 2017: 3036).…”
Section: Three Bodies Of Literaturementioning
confidence: 91%
“…The amount of money a victim received did not relate to either dimension. Kunst et al (2017) investigated how satisfaction with the services provided by the Dutch Fund may be mediated by victims' prior expectations of how they would be treated and what they might receive. Victims were interviewed by phone before and after they had received the money.…”
Section: Victims and Research On State-based Schemes: A Reviewmentioning
confidence: 99%